Space Security Dilemma: India and China. Issue 1 (2nd January 2019) - Lele, Ajey
ABSTRACT: There is an ongoing debate on an India-China space race. Both states have made investments in the space domain for the last few decades for social, scientific, commercial, and military reasons. The January 2007 anti-satellite test conducted by China significantly raised international concerns on issues concerning space security. China's strategic space program is witnessing major advances, and China's attainments in the space arena in terms of its financial investments, expanse of programs, technology proficiency, and future plans are ahead of those of India. At the same time, both states are pursuing programs such as the development of navigational networks and missions to the Moon and Mars. In this context, it is of interest to analyze China's increasing focus on satellite technologies and India's response. This article analyzes the possible manifestation of a "security dilemma" in the context of outer space among these states and concludes that the dilemma is suggestive, but not definitive.